High‐intensity swimming exercise reduces inflammatory pain in mice by activation of the endocannabinoid system. (18th June 2020) - Ludtke, Daniela D.; Siteneski, Aline; Galassi, Taynah de Oliveira; Buffon, Alexandre Carlos; Cidral‐Filho, Francisco José; Reed, William R.; Salgado, Afonso Shiguemi Inoue; dos Santos, Adair R.S.; Martins, Daniel F.
Abstract : As exercise intervention solely for pain reduction is relatively new, the available research still leaves an incomplete picture of responsible mechanisms and pathways. Nonetheless, evidence indicates that exercise‐induced analgesia involves activation of the endocannabinoid (eCB) system. The present study investigated the role of the eCB system on the antihyperalgesic effect of high‐intensity swimming exercise (HISE) in an animal model of peripheral persistent inflammation. Male Swiss mice were allocated to non‐exercised and exercised groups and subjected to subcutaneous intraplantar injection (i.pl.) of a single dose of complete Freund's adjuvant (CFA) to induce inflammatory pain. Cumulative HISE was performed once a day, and mechanical hyperalgesia and edema were evaluated 0.5 hour after HISE for seven consecutive days. To investigate the role of the eCB system on the antihyperalgesic effect of HISE, non‐exercised and exercised mice received intraperitoneal (ip), intrathecal (i.t.) or i.pl. injections of vehicle, AM281 (a CB1 cannabinoid receptor antagonist) or AM630 (a CB2 cannabinoid receptor antagonist) from the 3rd to 5th day after CFA injection. Mechanical hyperalgesia was evaluated 0.5 hour after HISE. In addition, the effect of the fatty acid amide hydrolase [FAAH] inhibitor or monoacylglycerol lipase [MAGL] inhibitor on the antihyperalgesic action of HISE was investigated. HISE reduced mechanical hyperalgesia with effects prevented by AM281 or AM630 pretreatment in all delivery routes tested. The inhibition of FAAH and MAGL prolonged the antihyperalgesic effect of HISE. These data demonstrate evidence for the role of the eCB system upon exercise‐induced analgesia in a murine model of inflammatory pain.